The origin of endorheic pans on the African erosion surface North of Grahamstown, South Africa - Alistoun, Judith Robyn (Rhodes University, Faculty of Science, Department of Environmental Science, 2014)
Pans on the African Erosion Surface near Grahamstown are small features, which, perhaps due to their small size have been neglected by researchers. From the outset the striking difference of these pans relative to other pans in southern Africa, is that the host rock is silcrete, a highly resistant rock well known as being associated with deeply weathered plateaus. The dominant origin theory for pans in southern Africa was developed by Goudie and Thomas (1985), and focuses on mechanisms relating to erosion and deflation. This model does not fit in well with the pans that have formed on substrate that has largely been unaffected by erosion in recent geological history (thousands to 10 000 years). As such this study examined the role of prolonged chemical weathering of Dwyka Tillite, that has led to the formation of silcrete. The hypothesis was that such deep weathering is responsible for local scale volume changes, which have in turn led to the formation of a depression. The centre of the pan indicated the highest concentration of Al₂O₃ and kaolinite at mid depths, and their concentrations decreased vertically away from these depths, and laterally towards the margins of the pan. Similar results were noted for SiO₂, while CaO and MgO (and calcite and dolomite) were highest at mid depths along the margins of the pan, and decreased laterally toward the centre of the pan. Results indicated that there was a positive relationship in the centre of the pan between: - the degree of chemical weathering and volume losses, - relative elevation of the pan and volume changes. Geochemically and mineralogically, there was a link between the high concentrations of Ca and Mg carbonates and volume gains in the margin of the pans. It is proposed that transpiration of vegetation along the margin of the pan caused the lateral movement of solutes, and the selective exclusion of these solutes by plants was associated with carbonate precipitation, leading to the creation of local relief. These results provide evidence to suggest that weathering and precipitation processes occurring over geological time scales are responsible for minor scale relief features, whose origin has been mistakenly attributed to deflation processes occurring over hundreds to thousands of years.
Keywords: Uncatalogued